Crystal structure of nitrogen regulatory protein IIA from Neisseria meningitidis - Sainsbury, S; Berrow, N; Alderton, D; Nettleship, J; Stammers, D; Owens, R; Ren, J; Saunders, N (2005)
Background: The NMB0736 gene of Neisseria meningitidis serogroup B strain MC58 encodes the putative nitrogen regulatory protein, IIA (abbreviated to NM-IIA). The homologous protein present in Escherichia coli is implicated in the control of nitrogen assimilation. As part of a structural proteomics approach to the study of pathogenic Neisseria spp., we have selected this protein for structure determination by X-ray crystallography. Results: The NM-IIA was over-expressed in E. coli and was shown to be partially monophosphorylated, as assessed by mass spectrometry of the purified protein. Crystals of un-phosphorylated protein were obtained and diffraction data collected to 2.5 Å resolution. The structure of NM-IIA was solved by molecular replacement using the coordinates of the E. coli nitrogen regulatory protein IIA [PDB: 1A6J] as the starting model. The overall fold of the Neisseria enzyme shows a high degree of similarity to the IIA from E. coli, and the position of the phosphoryl acceptor histidine residue (H67) is conserved. The orientation of an adjacent arginine residue (R69) suggests that it may also be involved in coordinating the phosphate group. Comparison of the structure with that of E. coli IIA complexed with HPr [PDB: 1J6T] indicates that NM-IIA binds in a similar way to the HPr-like enzyme in Neisseria. Conclusion: The structure of NM-IIA confirms its assignment as a homologue of the IIA proteins found in a range of other Gram-negative bacteria. We conclude that the NM- IIA protein functions as part of a phosphorylation cascade which, in contrast to E. coli, shares the upstream phosphotransfer protein with the sugar uptake phosphoenolpyruvate:sugar phosphotransferase system (PTS), but in common with E. coli has a distinct downstream effector mechanism. © 2005 Ren et al; licensee BioMed Central Ltd.